Asian primates in fragments: Understanding causes and consequences of fragmentation, and predicting primate population viability. Issue 4 (24th December 2019) - Boonratana, Ramesh
Abstract: Ongoing efforts to conserve the Asian primates are severely challenged by increasing rates of habitat loss and fragmentation. Underlying drivers such as rapid economic and population growth throughout much of South, East, and Southeast Asia have confined several populations of Asian primates to isolated fragments. Conservation efforts for these primates are partly hampered by a poor understanding of fragmentation, resulting in an inability to draw up effective long‐term conservation responses. In this manuscript, I show that fragmentation can be understood better when treated both as stress and a threat. Moreover, despite a myriad of causes of fragmentation reported, most are broad descriptions or subject to various interpretations. Here I describe the use of the IUCN‐CMP Unified Classifications of Direct Threats Version 3.2, a convenient and universal tool, for more precise identification of the causes and consequences of fragmentation for Asian primates. I further describe the interrelated variables influencing the persistence of Asian primates in fragments, and the conditions affecting these variables. Abstract : The threats of fragmentation and the variables influencing primate population viability. Threats causing and as a consequence of fragmentation, some underlying drivers to the threats, and how these threats impact primate population viability and ecological services; the interrelationships between the variables and their conditions, and how they influence primate population viability in fragments; and how knowing specific threats, their causes and consequences, and their underlying causes can guide better the development of appropriate conservation responses and mitigation measures. Research highlights: Fragmentation is both a stress and a threat to Asian primates. Employing universal tool standardizes the causes and consequences of fragmentation. Several interrelated features and conditions influence the viability of Asian primates in fragments.